In memoriam de Katiuska Contreras Yanez - Briones, Viteri (Revista Universidad de Guayaquil, 1998)
Although I have not known youLittle comet of light flying to the sky.Little snowy tree where the longest hopes nested.Happy goldfinch that did not recount time and joy.Crystal water where we washed our intimate misfortunes.Tender iron that united us forever.